MONITORING OF OXYGEN THERAPY IN ADULT HOSPITALIZED (Fiep Bulletin - online, 2014)
Introduction: The oxygen therapy consists in a treatment which the partial pressure of oxygen in arterial bloodis increased through greater concentration of oxygen in inspired air. Oxygen therapys could be indicated a curately for each individual, being used mainly in lower airway inflammation, respiratory failure and hypoxemia. Improper use can cause damage to the organism of individuals and high concentrations of oxygen generate free radicals, which can develop alterations in the central nervous system. Objectives: To describe the offer, modes and devices used in oxygen use in adults hospitalized. Method: The study included 40 subjects, 17 males and 23 females, aged between 21-89 years who were admitted in hospital making use of oxygen. Results: The mean FiO2 offered was 0,41 ± 0,08 SpO2 generating average 0,98 ± 0,02%, leading to an average of 119,15 ± PaO2 40 mmHg identifying hyperoxia in 60% of subjects. The main form of administration was oxigen circuit via mechanical ventilation and the use of masks. Conclusion: It was observed that the oxygen was offered in addition to the necessary individuals, generating an oxygen pressure above 100 mmHg generating hyperoxia, exposing the individuals to the harmful effects of the high oxygen concentration.
Keywords: Oxygen; Monitoring; Toxicity.